Bridging the gap from values to actions: a family systems framework for family-centered AAC services. (2nd January 2017) - Mandak, Kelsey; O'Neill, Tara; Light, Janice; Fosco, Gregory M.
Abstract: Despite the growing recognition of the importance of family involvement in augmentative and alternative communication (AAC) intervention, little guidance exists on how professionals can establish successful collaborative relationships with families. In this paper, we discuss family systems theory and ecological systems theory as a framework to guide family-centered AAC practice, review family-focused research in AAC, consider how AAC may impact the family system, and provide examples of the clinical implications of using the proposed family systems framework to improve family-centered AAC practice.